Carbon Potentials in Biomass of Fruit Trees in Home Gardens in the Bogor Regency, West Java - Dian Adijaya Susanto; Kuswata Kartawinata; Nisyawati (Journal of Tropical Ethnobiology, 2021)
A study using the point centered quarter method for trees and quadrats for saplings in homegardens of 41 hamlets within 40 districts in the Bogor Regency, West Java, revealed a rich diversity of fruit trees. Artocarpus heterophyllus, Nephelium lappaceum, Mangifera indica, and Durio zibethinus were the dominant and widely distributed fruit tree species. Above ground biomass of trees and saplings were calculated using allometric equations and the C (carbon) stocks were estimated by assuming that C constitutes 50% of biomass. The total biomass of trees with diameter at breast height ≥ 10 cm amounted to 1,081.7 tons, varied between hamlets from 10.1 to 66.7 tons/ha and the mean per hamlet of 26.4 ± 9.9 ton/ha, while that of saplings with diameter of 2 to 9.9 cm recorded to be 390.4 tons with a range between hamlets of 3.9 to 12.9 tons/ha and the mean per hamlet of 9.5 ± 3.7 tons/ha. The total aboveground C stocks was 540.9 tons for trees with a range between hamlets of 5.1 to 33.4 tons/ha and the mean per hamlet of 13.2 ± 4.9 tons/ha, while that of saplings was 195.2 tons with a range between hamlets of 0.7 to 9.4 tons/ha and the mean per hamlet of 4.9 ± 1.8 tons/ha. The main fruit trees with highest carbon sequestration capacity were Artocarpus heterophyllus, Mangifera indica, Mangifera foetida, and Sandoricum koetjape.